Bridging the Difference to the Billionth-of-a-Meter Length Scale: How to Operate Nanoscopic Machines and Nanomaterials by Using Macroscopic Actions - Ariga, Katsuhiko; Mori, Taizo; Ishihara, Shinsuke; Kawakami, Kohsaku; Hill, Jonathan P (Chemistry of materials, 2014)
Useful materials are generally required at the macroscale in bulk quantities, while nanotechnology handles nanosized objects. Fine functions based on nanoscopic systems operated by applying macroscopic stimuli could become a key process to access nanotechnological functions in our everyday lives. To bridge the gulf in dimension between the macroscale and molecular or nanoscale, we must develop a new methodological paradigm. In this short review, both leading examples and novel challenges of nanosystem controls are described including (i) operation of single molecular machines, biochemical machines, and supramolecular machines; (ii) functional control of nanostructured materials by applying stimuli such as light and heat; (iii) mechanical control of nanomaterials and molecular machines. In the latter subject, the importance of dimensional coupling at an interfacial environment is emphasized.